(untitled) (Physical Education, Health and Social Sciences, 2025)
Hormonal imbalance is one of the major causes that leads to a high risk of miscarriage. All the physiological processes required for the maintenance of pregnancy are disturbed due to this. Many hormones such as progesterone, thyroxine and triiodothyronine of the thyroid hormone family, prolactin, and cortisol, besides polycystic ovary syndrome, disturb normal healthy development of pregnancy. If the progesterone levels are inadequate, which is crucial in preparing the uterine lining and suppressing contractions in the uterus, implantation fails, or miscarriage occurs in early pregnancy. Thyroid dysfunction, either hypothyroidism or hyperthyroidism, can affect fetal growth and increase the risk of miscarriage. High levels of prolactin, which commonly occur in PCOS, inhibit ovulation and progesterone production, leading to pregnancy loss. Moreover, hormonal imbalances affect the immune system and uterine blood flow, which may impact fetal development by limiting the supply of oxygen and nutrients. This review aims to bring out how hormonal imbalance leads to miscarriage, the impact of various hormones on the maintenance of pregnancy and fetal development. It further deals with methods of diagnosing hormonal abnormalities and the importance of early intervention to improve pregnancies. Hormonal tests, such as blood tests for progesterone, thyroid hormones, prolactin, and others, are imperative in order to determine early risks. It is possible to make an early diagnosis before treatments like hormone supplementation lower the rate of miscarriage. Awareness of mechanisms that hormonal imbalance leads to miscarriage is key in improving the detection, interventions, and success rates of early pregnancies. Early diagnosis and treatment for women whose hormonal levels have been disrupted lead to reduced chances of pregnancy loss and healthy birth and motherly conditions.